2003
DOI: 10.1177/13591053030085007
|View full text |Cite
|
Sign up to set email alerts
|

Living with Diabetes in Rural and Urban Ghana: A Critical Social Psychological Examination of Illness Action and Scope for Intervention

Abstract: Current chronic illness research in Africa neglects the social psychological dimensions of illness experiences that present more appropriate frameworks for intervention. Informed by social representations theory, links between social knowledge of diabetes, illness experience and illness action were examined through semistructured individual interviews with rural and urban Ghanaians with diabetes. All respondents drew interchangeably from commonsense, scientized, and religious knowledge modalities in defining h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 22 publications
6
50
1
1
Order By: Relevance
“…Thus, a mixture of explanations was found that might be related to limited knowledge about DM, also evident in discussions concerning the pathophysiology of DM, action of drugs, and many were unable to identify the disease at the onset and suspected other diseases such as HIV, AIDS, malaria etc. The results confirmed previous findings in Ugandans [11] and concerning limited knowledge about DM in Africans [12-15]. The limited knowledge about DM is also reflected in self-care measures undertaken to restore and maintain health, as many had problems in identifying the causes of their health problems and frequently used supernatural measures (prayers, holy water) and natural factors (herbal remedies).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, a mixture of explanations was found that might be related to limited knowledge about DM, also evident in discussions concerning the pathophysiology of DM, action of drugs, and many were unable to identify the disease at the onset and suspected other diseases such as HIV, AIDS, malaria etc. The results confirmed previous findings in Ugandans [11] and concerning limited knowledge about DM in Africans [12-15]. The limited knowledge about DM is also reflected in self-care measures undertaken to restore and maintain health, as many had problems in identifying the causes of their health problems and frequently used supernatural measures (prayers, holy water) and natural factors (herbal remedies).…”
Section: Resultssupporting
confidence: 87%
“…Men focused on socio-economic factors, particularly the affordability of drugs, sexual function and lifestyle, while women valued well-being, support in daily life and household activities and had a higher risk awareness of DM. The indication of limited knowledge was in accordance with findings shown in previous investigations focusing on knowledge of DM in people in Cameroon and South Africa [12,13], and little understanding of the nature of DM, with reporting of a spectrum of different causes of DM in an investigation of the impact of the disease in Nigerians with DM [14], while in Ghanaians diagnosed with DM a blend of commonsense, scientized, and religious knowledge modalities that merged with biomedical goals, specifically drug and diet management [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Our findings support findings from other studies in Africa that demonstrate that the high cost of drugs makes it difficult for people living on low income to enjoy the full benefits of biomedical care (Aikins, 2005; Awah, Unwin, & Phillimore, 2008; BeLue et al, 2012; Hjelm & Beebwa, 2013; Hjelm & Mufunda, 2010; Popoola, 2005). Similar to our study, others conducted in sub-Saharan Africa demonstrate that economic barriers such as poverty make it difficult to afford drugs (Aikins, 2003, 2005; Popoola, 2005), disease monitoring supplies (Abdelgadir, Elbagir, Eltom, & Berne, 2006; Hjelm & Beebwa, 2013), and the recommended diet (Muchiri, Gericke, & Rheeder, 2012). …”
Section: Discussionsupporting
confidence: 88%
“…Although in Ghana, research has shown that diagnosis of chronic noncommunicable diseases often cause a disruption in family/social relationships (Kowal, Wolfson, & Dowd, 2000; de-Graft Aikins, 2003), and such forms of disruption affects the health of older adults due to their vulnerability during the later stages of life (Mavaddat, Valderas, van der Linde, Kay Tee, & Kinmonth, 2014), the current study found that diagnosis of chronic noncommunicable diseases does not impact on the SRH of older adults (Sander, 2002). The contradiction highlights the need to continue health intervention programs for older adults diagnosed with chronic noncommunicable diseases, a common disease associated with aging, as a deliberate measure to maintain the current finding (Phaswana-Mafuya et al, 2013b).…”
Section: Discussioncontrasting
confidence: 61%